Mock circulatory test rigs for the in vitro testing of artificial cardiovascular organs. (19th May 2019) - Shi, Yubing; Yang, Hongyi
Abstract: In vitro study plays an important role in the experimental study of cardiovascular dynamics. An essential hardware facility that mimics the blood flow changes and provides the required test conditions, a mock circulatory test rig (MCTR), is imperative for the execution of in vitro study. This paper examines the current MCTRs in use for the testing of artificial cardiovascular organs. Various aspects of the MCTRs are surveyed, including the necessity of in vitro study, the building of MCTRs, relevant standards, general system structure (e.g., the motion and driving, fluid, measurement subsystems), classification, motion driving mechanism of MCTRs, and the considerations for the modelling of the physiological impedance of MCTRs. Examples of the steady and pulsatile flow types of the MCTRs are introduced. Recent developments in MCTRs are inspected and possible future design improvements suggested. This study will help researchers in the design, construction, analysis, and selection of MCTRs for cardiovascular research.